Biosimilars in psoriasis: Clinical practice and regulatory perspectives in Latin America. Issue 1 (27th July 2016) - de la Cruz, Claudia; de Carvalho, André V. E.; Dorantes, Gladys L.; Londoño Garcia, Angela M.; Gonzalez, Cesar; Maskin, Matías; Podoswa, Nancy; Redfern, Jan S.; Valenzuela, Fernando; van der Walt, Joelle; Romiti, Ricardo
Abstract: Latin American countries view biosimilar agents as an effective approach to curtail health‐care expenditures while maintaining the safety and efficacy profile of their branded innovator comparators. To understand the complexities of the regulatory landscape and key therapeutic issues for use of biosimilars to treat moderate to severe psoriasis in Latin America, the International Psoriasis Council convened dermatology experts from Argentina, Brazil, Chile, Colombia and Mexico in October 2015 to review the definition, approval, marketing and future of biosimilars in each country and develop a consensus statement. The regulatory framework for marketing approval of biosimilars in Latin America is currently a mosaic of disparate, country‐specific, regulatory review processes, rules and standards, with considerable heterogeneity in clarity and specificity. Regulations in Argentina, Brazil, Chile and Mexico have undergone multiple refinements whereas Colombia is finalizing draft guidelines. Verification of the similarity in quality, safety and efficacy of biosimilars to the innovator biologic remains a key challenge for policy makers and regulatory authorities. Other key regulatory challenges include: naming of agents and traceability, pharmacovigilance, extrapolation of indications, and interchangeability and substitution. An urgent need exists for more Latin American countries to establish national psoriasis registries and to integrate their common components into a multinational psoriasis network, thereby enhancing their interpretative power and impact. A Latin American psoriasis network similar to PSONET in Europe would assist health‐care providers, pharmaceutical companies, regulators and patients to fully comprehend specific products being prescribed and dispensed and to identify potential regional trends or differences in safety or outcomes.